Analysis of The Effect of Change Orders on Implementation Time and Construction Labor Costs in The Development Project of The Joint Lecture Building III at Unimus - Rinaldi, Bramantyo; Suwandi, Putri Anggi Permata; Kristiawan, Agung (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
Change orders resulted in a total time deviation of 45 days (18.75%) from the initial plan, with the most substantial delays in structural and MEP work. Regarding labor costs, MEP work experienced the largest deviation at 25% (IDR 150,000,000), followed by foundation work (16.67%), structural work (15%), and architectural work (10%). Change orders also impacted labor productivity, particularly in MEP work (-25%), followed by foundation (-16%), structural (-12.5%), and architectural work (-12.5%). These productivity decreases resulted from changes in work methods, increased complexity, and adaptation requirements to new specifications. The study recommends several measures to minimize change order impacts: more thorough design reviews before implementation, allocation of time and cost buffers, improved documentation and approval systems, and more flexible workforce planning. Effective change order management is crucial for maintaining overall project success.